Homeopathic Treatment of Insomnia and Symptom Clusters Related to Cerebral Chemotoxicity in Oncology - Bagot, Jean-Lionel; Marechaud, Natalia; Deana, Nicolas; Wendling, Julie (Homeopathy, 2018)
Background During chemotherapy, the correlation between insomnia and fatigue, anxiety, pain, depressed mood, and cognitive disorders makes these subjective complaints a ‘symptom cluster’ with common biological mechanisms. The theory of cerebral inflammation following the production of pro-inflammatory cytokines (high level of interleukin 1-β [IL1-β], IL6 and tumour necrosis factor-alpha) is currently the most generally accepted. Understanding these mechanisms should allow us to propose a chemoprotective homeopathic treatment of the nervous system.Methods By retaining the inflammatory aetiology, we combined the rubrics ‘Inflammation of the brain’, ‘Inflammation of the meninges’, ‘Inflammation of the nerves’ with the symptom cluster: insomnia, fatigue, depressive state and memory disorders.Results After repertorisation, we propose the following homeopathic protocol: Belladonna 15c, Phosphorus 15c, Cerebral cortex 4c and Nerves 4c, two pills of each medicine to be sucked together before breakfast, lunch and dinner, on each day of chemotherapy and for the following 2 days.Conclusion This selected protocol, derived from a physiopathological knowledge of the symptoms, seems to be well suited to the prevention and treatment of post-chemotherapeutic cerebral inflammation. It is essential to start the homeopathic treatment before the chemotherapy session to anticipate the emergence of the ‘chemo-brain’ side effects. This proposed prevention protocol must be confirmed and quantified by randomised studies.
Keywords: Belladonna; cancer; cerebral chemotoxicity; fatigue; symptom cluster; homeopathy; insomnia; Phosphorus; supportive care